2022
DOI: 10.1093/burnst/tkac016
|View full text |Cite
|
Sign up to set email alerts
|

Non-severe burn injury increases cancer incidence in mice and has long-term impacts on the activation and function of T cells

Abstract: Background Recent evidence suggests that burn patients are at increased risk of hospital admission for infection, mental health conditions, cardiovascular disease and cancer for many years after discharge for the burn injury itself. Burn injury has also been shown to induce sustained immune system dysfunction. This change to immune function may contribute to the increased risk of chronic disease observed. However, the mechanisms that disrupt long-term immune function in response to burn traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Teisserenc et al revealed the functional impairment of NK cells during burn injuries and its association with septic shock after burning 105 . However, Barrett et al 106 demonstrated that non-sever burn injuries didn’t impact NK cell activities, and accordingly, burn severity can be an influential factor on NK cell activity or count. Also, inconsistent with our findings, Devine et al 107 showed an extreme count reduction of NK cells after severe burn injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Teisserenc et al revealed the functional impairment of NK cells during burn injuries and its association with septic shock after burning 105 . However, Barrett et al 106 demonstrated that non-sever burn injuries didn’t impact NK cell activities, and accordingly, burn severity can be an influential factor on NK cell activity or count. Also, inconsistent with our findings, Devine et al 107 showed an extreme count reduction of NK cells after severe burn injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous study, we constructed a burned mouse model [ 41 ]. Briefly, the 1% pentobarbital sodium (40 mg/kg) was used to anesthetize mice; the hair on the back of mice was removed with a razor and coated with hair removal cream for 20 s. Additionally, the cream was gently wiped away with medical gauze soaked with PBS so that the exposed area was about 30% of the total surface of the body.…”
Section: Methodsmentioning
confidence: 99%